Irreversible binding to the receptor of bacteriophages T5 and BF23 does not occur with the tip of the tail. - Heller, K J (1985)
Treatment of purified tails of bacteriophage T5 with 0.05% sodium dodecyl sulfate specifically removed pb2, a protein of 108,000 molecular weight (108K), from the tail. Although these tails were devoid of the single straight tail fiber, they still inhibited adsorption of T5 to Escherichia coli cells. Reconstitution of these tails with pb2 increased the efficiency of inhibition of T5 adsorption. Treatment of tails with 0.1% sodium dodecyl sulfate removed, in addition to pb2, a protein of 67K from phage T5 and one of 60K from phage BF23. These tails failed to inhibit phage adsorption, and no reconstitution was achieved. Reconstitution of T5 tails with pb2 from BF23, and of BF23 tails with pb2 from T5, did not alter the host receptor specificity of the tails. Binding of untreated T5 tails to small FhuA receptor particles revealed that binding occurred with the conical part of the tail and that pb2 was most likely released from the tail upon binding. From these results and from recent observations with T5-BF23 hybrid phages (K.J. Heller, Virology 139:11-21, 1984), we conclude that the receptor-binding proteins of T5 and BF23 are the 67K and 60K proteins, respectively, and that they are not located at the tip of the tail but rather at or near the site where the straight tail fiber is attached to the conical part of the tail.